Citizen Oversight through Social Accountability : The Malawi Social Action Fund and the Comprehensive Community Scorecard Process - Kajumi, Murphy (World Bank, Washington, DC, 2012)
The Third Malawi Social Action Fund Project (MASAF 3) was designed in the context of the Malawi Government's Poverty Reduction Strategy (PRS) of April 2002. The PRS had the following four pillars: (a) sustainable pro-poor economic growth to empower the poor by ensuring access to credit and markets, skills development and employment generation; (b) human capital development to ensure that the poor have the health and education status to lift themselves out of poverty; (c) improving the quality of life for the most vulnerable by providing sustainable safety nets for those who are unable to benefit from the first two pillars; and (d) promotion of good governance, political will and mindset which will ensure that public and civil society institutions and systems protect and benefit the poor.